Employability skills constructs as job performance predictors for Malaysian polytechnic graduates: a qualitative study - Normala Rahmat; Abdul Rahman Ayub; Yahya Buntat (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The acquisition of employability skills that match and fit the employers’ requirement would enhance employees’ job performance. This study explored and factorized the constructs and dimensions of employability skills which can predict the job performance of Malaysian electric and electronic polytechnic graduates in the electrical and electronics industry. A qualitative approach was used in the development of the research Employability Skills Work Performance Prediction (ESWPP) constructs and dimensions starting from relevant document analysis and expert interviews. The ESWPP constructs and dimensions were then validated by content experts from academic institutions. Finally, the findings were analyzed using the Fleiss Kappa reliability analysis to determine the overall approval index for each of the ESWPP constructs and dimensions. Results of the analysis revealed an overall Kappa coefficient value of 0.989 which indicated a very good level of agreement . The ESWPP constructs and dimensions which were found to be job performance predictors were communication skills, personal qualities, teamwork skills, critical thinking and problem solving skills, technology skills, organizational skills, and continuously learning skills.